Middle atmosphere Aerosols, Dynamics and Monsoon Variability: a Review - Joshi Indira Sudhir; Devara P.C.S. (International Journal of Research in Chemistry and Environment (IJRCE), 2012)
Some dynamical parameters of the middle atmosphere such as quasi-biennial oscillation in the low-latitude stratospheric zonal winds, interannual variability of the high-latitude middle atmosphere and stratospheric warming in the tropical middle atmosphere are studied to examine their roles in determining the variability of rainfall over India during the summer monsoon season. It is believed that the amount of sulphurous gases released into the stratosphere from the great volcanic eruptions modulates the climate (rainfall). The authors have made an attempt in this paper to present a review of the work done so far in this direction.